Technology supported early literacy learning in a multilingual community preschool. Issue 6 (18th August 2019) - McGlynn-Stewart, Monica; Murphy, Shelley; Pinto, Ivorie; Mogyorodi, Emma; Nguyen, Thien
ABSTRACT: There is conflicting research on the value of using digital technology with young children. This study investigated how an app, used in conjunction with dual language picture books, can support the social, emotional, and literacy learning of bi/multilingual children. Twenty-one children used the app Talking Stickers at home and school for four weeks. The classroom was observed and the educators and parents were interviewed and surveyed. The findings indicated that children had enhanced opportunities to practice social, cognitive, and multi-lingual literacy skills, and bonds between home and school were strengthened. The research has implications for classroom practice and home-school programmes.